The Moderating Role of Institutional Ownership on the Relationship between Financial Determinants and Tax Aggressiveness - Addhea Herlita; Eva Herianti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Purpose: This study examines the influence of profitability, thin capitalization, and capital intensity on corporate tax aggressiveness, with institutional ownership as a moderating variable, in mining companies listed on the Indonesia Stock Exchange during 2020–2024. Methodology: This study adopts a quantitative approach using secondary data from the financial statements of 34 mining firms listed on the Indonesia Stock Exchange (2020–2024), selected through purposive sampling. Panel data regression was performed using Stata version 17, and model specification tests confirmed the random effect model as the most appropriate method, capturing firm-level variations while accounting for unobserved heterogeneity. Findings: The results reveal that profitability (ROA), thin capitalization (DER), and capital intensity (CAPIN) significantly affect tax aggressiveness. Profitability and thin capitalization exhibit a negative relationship, implying that higher profitability and leverage reduce aggressive tax practices. Conversely, capital intensity shows a positive relationship, suggesting firms with larger fixed assets utilize depreciation for tax minimization. Institutional ownership (INS) does not significantly moderate these relationships, indicating limited monitoring effectiveness. Implication: The findings imply that regulators should enhance oversight of profitable and capital-intensive firms to prevent excessive tax aggressiveness, while managers must balance tax efficiency with ethical responsibility. Strengthening institutional investor involvement in monitoring corporate tax behavior can also promote transparency and long-term fiscal sustainability. Originality: This study enriches the literature by identifying institutional ownership as a moderator of homologization in the relationship between financial characteristics and tax aggressiveness, highlighting the conditional nature of governance mechanisms in emerging markets. This study also incorporates empirical case phenomena related to PT Aneka Tambang (Antam) taxes to contextualize corporate tax behavior, while using Stata version 17 for robust panel data analysis.